Spatial Environmental Services in the Approach of the Assumptions of Economics for Sustainable Development - Michałowski, Artur (Problemy Ekorozwoju, 2011)
The aim of this paper is to present the economic problems of the spatial environmental services in the emerging economy of sustainable development. Its theory has interdisciplinary bases. It is taking into account the achievements of many scientific fields, including spatial management, environmental economics and ecological economics. So far, in case of the ecological and economic problems, most attention was paid to the exploitation of natural resources, the production of environmental goods and environmental determinants of economic growth. Now it became necessary to extend ecological-economic analysis and include environmental services, which represent one of the bases for the functioning of environment-economy-society macrosystem. In fact, there is no real economy without ecological processes connected with environmental services, including the spatial environmental services.